Ameliorate English Descriptive Writing Skill: Context Analysis - Nicodemus Bisse; Andi Sadapotto (Universitas Muhammadiyah Enrekang, 2021)
The objective of the article is to explore the use of context analysisameliorate the ability of the students at SMP Negeri1Pancarijang to write descriptive composition and to find out students’ interest in learning writing the descriptive composition by using context analysis at the eighth grade student SMP Negeri1Pancarijang. This research employed the method of the research was pre-experimental method with one group pre-test and post-test design. The population was the eighthgrade student of SMP Negeri1Pancarijang in 2020-2021academic years. class VIII.a (24) was chosen as a sample. The instrument used in this research was to write descriptive composition and questionnaire to measure students’ interest. The result of this research showed that the pre-test got the mean score (53.12) while the post-test got mean score (78.91). This showed that there was significant difference between pre test and post test.The result of the P-value (0.000) was lower than level of significant (alpha (α)=0.05). This means that H1 was accepted. The research concluded that teaching writing by using context analysis increased the students’ ability to write descriptive composition at the eighth grade student of SMP Negeri1Pancarijang, and the result of students interest showed that from 24 respondents and total score 2.096 got mean score 87.33 was categorized in strongly interested. It proven that students at the second year of SMP Negeri1Pancarijang interested to learn write descriptive composition by using context analysis.